Effects of Intravenous Zoledronate on Bone Turnover and Bone Density Persist for at Least 11 Years in HIV‐Infected Men. (29th May 2019) - Bolland, Mark J; Horne, Anne M; Briggs, Simon E; Thomas, Mark G; Reid, IanR; Gamble, Greg D; Grey, Andrew
Abstract: Previously we reported the results of a 4‐year extension of a 2‐year randomized placebo‐controlled trial showing that the antiresorptive effects of two annual 4‐mg doses of zoledronate in HIV‐infected men persisted for at least 5 years after the second dose. We set out to determine whether the effects on BMD and bone turnover persist beyond 10 years. We invited all participants in the original trial known to be alive and living in New Zealand to attend an additional visit approximately 12 years after trial entry and 11 years after their second dose of study medication. The outcome measures were BMD at the lumbar spine, proximal femur, and total body, and markers of bone turnover. Twenty‐five of the 43 men originally enrolled in the trial attended the final visit, representing 25 of 31 (81%) participants alive and residing in New Zealand at the time. The average duration of follow‐up was 12.4 years. At the final visit, BMD remained higher in the zoledronate group than the placebo group (lumbar spine 3.7%, 95% CI, 0.1 to 7.3; total hip 3.7%, 95% CI, 1.2 to 6.2; femoral neck 5.0%, 95% CI, 2.1 to 7.9; total body 2.4%, 95% CI, 0.7 to 4.0), and the between‐group differences in BMD remained stable between 6 and 12 years. Serum CTx remained lower in the zoledronate group than the placebo group between 6 and 12 years and, at the final visit, was 45% lower (95% CI, 25 to 64) than the placebo group. P1NP was 26% (95% CI, 4 to 48) lower in the zoledronate group than the placebo group at the final visit. In summary, two annual 4‐mg doses of zoledronate have effects on bone turnover and BMD in men that persist for at least 11 years after the second dose. © 2019 American Society for Bone and Mineral Research.